Advanced Imaging Technology Other than Narrow Band Imaging - Jun-Hyung Cho (Korean Society of Gastrointestinal Endoscopy, 2015)
To improve the detection rate of gastrointestinal tumors, image-enhanced endoscopy has been widely used during screening and surveillance endoscopy in Korea. In addition to narrow band imaging (NBI) with/without magnification, various types of electronic chromoendoscopies have been used, including autofluorescence imaging, I-scan, and flexible spectral imaging color enhancement. These technologies enable the accurate characterization of tumors because they enable visualization of microvascular and microsurface patterns. The present review focuses on understanding the principle and clinical applications of advanced imaging technologies other than NBI.